Implementasi Monitoring Sistem Perusahaan On-Premises dan Cloud Menggunakan Teknologi Jenkins - Adil, Sinatria Banyu; Beeh, Yos Richard (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This research implements Jenkins for monitoring and managing job processes, as well as its integration with on-premises and cloud infrastructures at PT. AAA. Compute Engine is used as the main server to run Jenkins. The stages include configuring the Compute Engine server, installing important plugins, and using Python libraries. The results show that Jenkins successfully runs job processes between on-premises and cloud systems. The Email Extension Plugin is used to monitor job processes and send notifications to PICs in case of errors. Access management is implemented through Role-based Authorization Strategy. Testing is done using blackbox testing with a success rate of 100%. It is hoped that this implementation can improve the efficiency and effectiveness of job process management at PT. AAA.